Original paperBIOCHEMICAL CHANGES AND ENDOCRINE RESPONSES IN PRE-COMPETITION TRAINING IN ELITE SWIMMERS - Li, Y.; Zhu, Y.; Zhang, J.; Zhang, X.; Zeng, Y. (Biology of Sport, 2012)
The aim of this study was to describe biochemical changes and endocrine responses to low-volume pre-competition swimming training for elite swimmers. Twelve sprint swimmers (6 males and 6 females) participated in 3-week pre-competition training. Measures of velocity anaerobic threshold (VAT), creatine kinase (CK), blood urea (BU), haemoglobin (Hb) and testosterone/cortisol ratio (TC) were obtained before and after the 1st, 2nd and 3rd week of training. The training load decreased from 27.3 to 13.7 km per week within 3 weeks. The VAT tested the load with an increased training protocol of 200 m×4 freestyle swimming and initial loads were 85, 90, 95, and 100 percent of the individual load. There were changes in the values of VAT, CK, BU, Hb and TC ratio during the training, and the changes corresponded to the changes of the training stimuli in time. There were also differences between the male and female swimmers. The most significant finding in this study was that such training stimulated the enginery of the swimmers and helped the swimmers recover enginery and indicated improved velocity in the competition with the following adjusting exercise after pre-competition training.